Healthcare discrimination and factors associated with gender-affirming healthcare avoidance by transgender women and transgender men in Thailand: findings from a cross-sectional online-survey study - Nachale Boonyapisomparn; Natthaporn Manojai; Pimwarat Srikummoon; Walaithip Bunyatisai; Patrinee Traisathit; Nontiya Homkham (International Journal for Equity in Health, 2023)
Abstract Background Although discriminatory experiences of transgender people seeking healthcare services have been well-documented in several studies, differentiating those experiences based on gender identity/expression and related factors has been limited. The aim of this study was to compare the characteristics, experiences, attitude, and expectation toward accessing healthcare service and healthcare providers of transgender women and transgender men in Thailand. Methods A cross-sectional study was conducted from October 2017 to March 2018. The data were collected from transgender women and transgender men aged ≥ 18 years old who lived in Thailand using online platform via different websites and Facebook pages of local transgender group. Binary logistic regression was used to identify the factors related to the study outcomes. Results Of 186 transgender people who responded to the questionnaire and were eligible for the study, 73.7% (95% confidence interval [CI] = 66.7–79.8) were transgender women and 26.3% (95% CI = 20.2–33.3) were transgender men. Transgender women were more likely to seek general healthcare from non-traditional healthcare services (crude odds ratio [cOR] = 4.28; 95% CI = 1.55–11.81; P = 0.005), buy hormone treatment from non-traditional healthcare services (cOR = 3.89; 95% CI = 1.18–12.83; P = 0.026), and receive healthcare counseling from non-traditional healthcare providers (cOR = 5.16; 95% CI = 1.42–18.75; P = 0.013) than transgender men. According to the results of applying a multivariable model, transgender respondents who did not know that gender-affirming healthcare services existed in Thailand were more unwilling to receive counseling from gender-affirming healthcare providers than those who did (adjusted odds ratio = 3.70; 95% CI = 1.11–12.36; P = 0.033). Conclusions The findings from this cross-sectional study indicate that transgender women are more likely than transgender men to receive general healthcare and hormone treatment from non-traditional healthcare services and buy hormone treatment without a physician’s supervision. We also found approximately 15% of transgender individuals who did not receive gender-affirming counseling services. Continuing to improve access to care for the transgender community, increasing public relations channels may encourage transgender people to access more healthcare services.